Single-Stop Ebook Reader "SimplyE": Is It APPlicable for Academic Libraries?. Issue 2 (3rd April 2017) - Beswick, Kevin; Khan, Nushrat; Lewis, Danica
ABSTRACT: Accessing ebooks from different vendors often requires switching between multiple platforms, which can be unwieldy for library users. To offer readers a coherent and seamless reading experience, the New York Public Library (NYPL) initiated a project called SimplyE (or LibrarySimplified). The end user deliverable of this project is an application (Android, iOS) that enables users to read ebooks from multiple vendors through a single interface, thereby delivering a Netflix-style experience for searching, browsing, and checking out ebooks. The back end consists of applications that manage ebook collections, circulation, and metadata for libraries. This column explores the viability of implementing SimplyE in an academic library setting.